POLG Novel Mutation with Alpers Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at University Hospital, Berne, Switzerland describe the molecular genetic analysis of POLG in a 3.5 years old boy with VPA-induced fatal liver failure and encephalopathy (Alpers-Huttenlocher syndrome, AHS).